Ecdysis of three species of Krait (Bungarus: Elapidae: Squamata) in captivity, Bangladesh (Bangladesh Journal of Zoology, 2026)
The ecdysis of three species of Kraits (Bungarus caeruleus, B. niger and B. walli) was studied in captivity from October 2006 to January 2012. Kraits molted in regular intervals. B. walli molted more frequently than B. caeruleus and B. niger. The ecdysis interval days was higher in winter but was more frequent in other times of the year and it was the highest in March. Body colors of all species become dull before 7-8 days of molting (n=5). B. niger was more active before and after molting whereas other two species were less active. Climatic factors showed weak positive correlations with shedding during this study (temperature: r = 0.22, rainfall: r = 0.13, and humidity: r = 0.17) but these physical factors did not significantly influence the shedding of the studied species (p > 0.05).Bangladesh J. Zool. 53(3): 349-355, 2025